2020
DOI: 10.21037/jgo.2019.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Combined endo-laparoscopic surgery for difficult benign colorectal polyps

Abstract: Prevention of colorectal cancer (CRC) depends largely on the detection and removal of colorectal polyps. Despite the advances in endoscopic techniques, there are still a subgroup of polyps that cannot be treated purely by endoscopic approach, which comprise of about 10-15% of all the polyps. These so-called "difficult colorectal polyps" are polyps with large size, morphology, at difficult location, scarring or due to recurrence, which have historically been managed by surgical segmental resection. In treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…To date, few studies have described the use of various CELS techniques 16–20 . Reported technical success rates from available literature range from 95% to 100%, 16,18–20 comparable to ourtechnical success rate of 93%.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…To date, few studies have described the use of various CELS techniques 16–20 . Reported technical success rates from available literature range from 95% to 100%, 16,18–20 comparable to ourtechnical success rate of 93%.…”
Section: Discussionmentioning
confidence: 72%
“…A recent systematic review of CELS involving 101 patients showed no intra- or post-operative complications 17 . Another recent retrospective cohort study (n = 115 patients) showed Clavien-Dindo grade I-II complications in 13% of patients after CELS 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Some smaller, but more recent, studies showed lower complication rates [ 27 , 28 ]. In 2016 [ 29 ] and 2020 [ 30 ] systematic reviews were published with available literature on all combined endoscopic and laparoscopic surgery‐type procedures. All these included studies showed similar numbers of patients and results.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure with little modification is reported by Leicher et al [ 19 ] for “difficult” polyps in terms of location—cecum, hepatic flexure, splenic flexure and sigmoid colon. Polyps of the cecum are considered and described in the literature as “difficult” because of their location and the proximity of the ileocecal valve [ 3 ]. These lesions were usually treated by open surgery, but nowadays, with the introduction of endoscopically assisted laparoscopic procedures, many of these lesions could be resected laparoscopically, as we described here.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was firstly used for common bile duct stone treatment [ 1 ] but was introduced in other gastrointestinal (GI) areas as well. In GI surgery, this procedure is used for lesions that, for some reason, could not be resected completely endoscopically [ 2 ] or in laparoscopic procedures in which endoscopic navigation is necessary [ 3 ]. Endoscopic navigation is used in this technique for accurately determining the surgical field of work.…”
Section: Introductionmentioning
confidence: 99%